Differences in risk factors and resource utilization for women undergoing percutaneous coronary intervention and lower extremity peripheral vascular intervention. Issue 1 (9th August 2019) - Doshi, Rajkumar; Patel, Krunalkumar; Desai, Rupak; Patel, Palakkumar; Grines, Cindy; Meraj, Perwaiz
Abstract: Objective: To investigate the differences in risk factors and in‐hospital outcomes for women undergoing percutaneous coronary intervention (PCI) and peripheral vascular intervention (PVI). Background: The clinical impact of coronary artery disease (CAD) and peripheral artery disease (PAD) is well characterized and is associated with high morbidity and mortality. There is lack of data comparing risk factors and in‐hospital outcomes for PCI and PVI, particularly in women. Methods: Only female hospitalizations (age ≥ 18 years) who underwent PCI or PVI from 2005 to 2014 were identified using appropriate International Classification of Diseases‐Ninth Revision, Clinical Modification codes from the National Inpatient Sample database. Charlson's Comorbidity Index (CCI) was selected as the primary endpoint of the study. Coprimary endpoint was the cost of hospitalizations associated with PCI or PVI. Results: Of the 2, 461, 328 female hospitalizations that were included, 85.6% ( N = 2, 105, 236) underwent PCI and 14.4% ( N = 356, 092) received PVI. Compared to PCI, PVI hospitalizations were 3.2 years older ( p  < .001) and consisted of significantly more hospitalizations above 80 years of age (26.5% vs. 18.6%; p  < .001). Hospitalizations with CCI ≥3 were significantly higher in the PVI cohort (29.1% vs. 24%; p  < .001). CCI in women increased during the study period for both groups. PVI hospitalizations had a significantly longer length of stay (3 days vs. 2 days; p  < .001) and cost of hospitalization ($23, 610 vs. $20, 571; p  < .001), compared to PCI. Finally, the mean cost of hospitalizations increased during the study period for PCI and PVI. Conclusion: Women hospitalized for PVI had a greater risk‐profile and resource utilization as demonstrated by the longer length of stay and higher cost compared to PCI.